(untitled) (Iranian Journal of Kidney Diseases, 2017)
In the past 3 decades, ultrasonography has gifted internal organs visualization to physicians to have a better detection of various diseases. Previously performed solely by radiologists as a method with high feasibility and accuracy, recently ultrasonography is being recommended and used by many other physicians in practice. Ultrasonography not only can be used to diagnose and manage kidney diseases, but also is an essential tool in nephrology for the guidance of invasive procedures. This method of bedside ultrasonography by physicians in real time is called point-of-care ultrasonography (POCUS). Given the limitations of collecting information by routine physical examination in kidney diseases and the simplicity of performing ultrasonography to examine kidney location, architecture, and restricted pathologies, nephrologists that have been lagging in this area, should join the spectrum of clinicians using the POCUS to provide safe and rapid diagnosis of common renal abnormalities. Although physicians may imagine POCUS as a difficult tool to use and there has been an initial resistance and reluctance to use ultrasonography by nonradiologists, investigations have shown that learning and doing POCUS was possible even for undergraduate medical students during a short course. According to the collected evidence in the field of POCUS in different branches of medicine, it seems that it should be added to nephrology examination room in the near future.